The Effectiveness of Comic Strips in Teaching Adjectives at SMPN 1 Boyolangu - Aditya Fajrul Falah; Dina Kartikawati (STKIP PGRI Trenggalek, 2023)
English is a language that used to communicate around the world. The goal of learning English for the students is to be able to communicate in English. The objective of this research is to see the significant effect of comic strips to adjective mastery of first grade students at SMP Negeri 1 Boyolangu. This research has a quantitative, pre-experimental design with pre and post-tests for one group. The statistic shows mean of pre-test (39.7222%) and post-test (83.4722%). This research took 36 students as sample. The results reveal that the mean for the pre-test and post-tests is (-43.750), the standard deviation is (27.318), and the standard error mean is (4.553). The t-test result was (-9.609), with a df of 35 and a significance level of 0.000. The t-test result demonstrates that the significant value in the computation is 0.000 lower than 0.05. It means that the alternative hypothesis was accepted and the null hypothesis was rejected. It implies that the students’ score would be greater if comic strips had been used in their instruction.